Predicting the wear coefficient and friction coefficient in dry point contact using continuum damage mechanics. (March 2019) - Ghatrehsamani, Sahar; Akbarzadeh, Saleh
Wear coefficient and friction coefficient are two of the key parameters in the performance of any tribo-system. The main purpose of the present research is to use continuum damage mechanics to predict wear coefficient. Thus, a contact model is utilized that can be used to obtain the friction coefficient between the contacting surfaces. By applying this model to the continuum damage mechanics model, the wear coefficient between dry surfaces is predicted. One of the advantages of using this model is that the wear coefficient can be numerically predicted unlike other methods which highly rely on experimental data. In order to verify the results predicted by this model, tests were performed using pin-on-disk test rig for several ST37 samples. The results indicated that the wear coefficient increases with increasing the friction coefficient.